A novel approach for 3D morphological characterization of silica nanoparticle population through HAADF-STEM. (August 2021) - Crouzier, Loïc; Pailloux, Frédéric; Delvallée, Alexandra; Devoille, Laurent; Feltin, Nicolas; Tromas, Christophe
Graphical abstract: Highlights: Image processing method for 3D characterization of nanoparticles using HAADF-STEM. Proposed method applicable to chemically homogeneous particles. Proposed method validated by comparison with AFM/SEM hybrid approach. 3D characterization approach implemented for silica particles of more complex shape. Abstract: The morphology of amorphous silica NPs in three dimensions (3D) of space is analysed using a single technique: the transmission electron microscope in Scanning Transmission Electron Microscopy with High Angle Annular Dark Field (HAADF-STEM) imaging mode. For this purpose, a method consisting in adjusting the HAADF-STEM signal by a function describing the thickness of material in a sphere has been developed to determine the height of the nano-object and tested on particles having quasi-spherical shape. This approach is suitable only in the case of a nanomaterial chemically homogeneous. A reference present in the image is required for calibrating the signal strength. This reference can be either a particle of known shape or a particle whose height was previously measured with another technique ( i.e. Atomic Force Microscopy). Thus, the study of the small silica particles by HAADF-STEM highlighted their spheroidal shape but also their preferential orientation on the substrate.